The relation ship between curriculum and cognitive preferences - Chiam, Heng Keng (Education quarterly.)
This study is interested in exploring the relationship between the chemistry curriculum and cognitive preferences of Malaysian students. Cognitive Preference Test (CPT) was administered to 199 students who had just entered a pre-university college after completing secondary education. Eighty-one students were from the traditional chemistry course while 118 of them were from modern chemistry stream: 21 % and 25 % were girls respectively. The evidences in this study indicate that the cognitive preferences of students are much influenced by what is taught and how it is being taught.